In-situ assessment of the emissivity of tungsten plasma facing components of the WEST tokamak. (December 2020) - Gaspar, J.; Aumeunier, M.-H.; Le Bohec, M.; Rigollet, F.; Brezinsek, S.; Corre, Y.; Courtois, X.; Dejarnac, R.; Diez, M.; Dubus, L.; Fedorczak, N.; Houry, M.; et al.
Highlights: In-situ method to measure the plasma facing components emissivity. Non-uniform emissivity measured along the divertor W-coated components. Implication of non-uniform emissivity on heat flux estimation. Abstract: In this paper, a method was developed to estimate in-situ the emissivity of the W-coated graphite divertor tiles in the WEST tokamak. This method is based on the double heating method and take advantages of the divertor temperature increase after successive plasma experiments due to the inertial behavior of the plasma facing components. Photonic calculations have been used to disentangle the emitted and the reflected parts in the measured radiances from the infrared system. The uncertainty as well as the robustness of the method have been investigated thanks to the wide IR and thermocouple coverage in the WEST divertor. The results show strong variation of the emissivity along the divertor W surfaces with a factor 4 variation after the experimental campaigns including 18.3 GJ and about 21 000 s of cumulated injected energy and duration, respectively. Finally, the implication of a non-uniform emissivity on heat flux estimation from IR measurements is discussed, showing that non-uniform emissivity must be considered to obtain an accurate heat flux decay width.